Legal Framework for Regulation of Labor Migration From Ukraine to the Republic of Poland in the Conditions of COVID-19 - Astramowicz-Leyk, Teresa; Turchyn, Yaryna; Ivasechko, Olha (PRAWO i WIĘŹ, 2022)
The authors analyse the problem of normative and legal regulation of labor migration from Ukraine to the Republic of Poland in the conditions of COVID-19. They study the phenomenon of legislative regulation of migration policy in the examples of Ukrainian and Polish experiences. They especially consider the extensive, but at the same time insufficiently, developed the regulatory framework of Ukraine on migration issues. In addition, they highlight the consequences of the impact of the COVID-19 pandemic on the formation of normative and legal support for the labor migration of Ukrainians to Poland. The authors also discuss Polish successful practices in ensuring orderly and secure migration, and bilateral cooperation between Ukraine and Poland in the field of settlement of migration flows and threats. The difference in the national approaches of migration policies of Ukraine and Poland regarding the prompt solution of urgent problems of the migration sphere in a pandemic is highlighted. The authors conclude that it is necessary to form a new integrated migration policy for Ukraine taking into account the positive practices of the Polish approach in this area.